Core-shell GaSn@rGO nanoparticles as high-performance cathodes for room-temperature liquid metal batteries. (August 2022) - Wang, Kaizhao; Hu, Jin; Chen, Tianyou; Wang, Kaijun; Wu, Jun; Zhang, Weijun; Deng, Zhongshan
Abstract: Gallium-based liquid metals with high specific capacity and good self-healing properties are promising cathode materials for room-temperature liquid metal batteries (LMBs). Most liquid metal cathode materials, however, face critical challenges, including the large volume expansion, unstable solid electrolyte interface (SEI) layer, and serious capacity decay. Here, a facile coating strategy is shown to prepare GaSn nanoparticles encapsulated by reduced graphene oxide (rGO) with core–shell structures that exhibit high structural integrity and excellent electrochemical performance. The pleated rGO shell (≈6 nm) offers superior buffering properties and a stable SEI layer during charging and discharging processes, achieving excellent cycling stability. In situ X-ray diffraction patterns reveal that this novel GaSn@rGO NP electrode is based on an alloying/dealloying lithium storage mechanism. This study demonstrates that the rationally designed cathode material offers an unprecedented opportunity for room-temperature LMBs with high rate capability and cycling stability. Graphical Abstract: Image, graphical abstract